ICU Nurse Perspectives on Influences of Minimal Physical Restraint Practices: A Mixed‐Methods Study - Hui He; Jing Zhang; Liping Bai; Mengdi Zhang; Yu Chan Chen; Jing Liao (Nursing in Critical Care, 2026)
ABSTRACT Background Physical restraint is still common in Chinese intensive care units, especially for mechanically ventilated patients and those with invasive devices. Inappropriate use causes considerable physical and psychological harm. Despite global efforts to minimise restraint, systematic research on standardised assessment and management frameworks for restraint reduction in domestic ICUs is lacking. Aims This study aimed to explore the influencing factors of nurses' implementation of minimising physical restraint and identify key pathways for optimising clinical restraint management practices. Study Design This exploratory sequential mixed‐methods study (Qualitative→Quantitative) was conducted from July to November 2024 and recruited ICU nurses from three Grade 3 Class A tertiary hospitals, the highest hospital tier in southern China. Qualitative data from semi‐structured interviews were analysed using Colaizzi's phenomenological method. The core themes identified were then operationalised as antecedent conditions for fuzzy‐set qualitative comparative analysis (fsQCA). Only frontline bedside nurses were included in the fsQCA dataset, as they are the staff directly applying physical restraints. All procedures follow the MMARS (JARS‐Mixed) and GRAMMS reporting standards for mixed‐methods research. Results Six key themes emerged across patient, nursing and organisational levels. A single configurational pathway explained higher restraint removal rates (≥ 50%, based on published Chinese ICU data): the synergy of patient cooperation and effective staffing, combined with lower device‐related concerns, less clinical experience and limited team communication (consistency = 0.89, coverage = 0.34). Conclusions This study proposes the delivery of targeted training in the assessment of patients' level of consciousness, optimised nurse–patient ratio, improved physicians' and nurses' competence, and updated protocols to promote restraint minimisation in the ICU. Relevance to Clinical Practice Identifying barriers and facilitators to minimal restraint enables nurses to develop targeted strategies that ensure a safer work environment and promote patient‐centred care.